Bio-inspired intent communication for automated vehicles. (July 2021) - Oudshoorn, Max; de Winter, Joost; Bazilinskyy, Pavlo; Dodou, Dimitra
Highlights: Bio-inspired external human-machine interfaces (eHMIs) were tested online. The bioinspired eHMIs relied on principles from nature: posture, gesture, body colouration. 1141 participants viewed videos depicting a (non-)yielding automated vehicle. Traditional eHMIs were found to be more intuitive than the bio-inspired eHMIs. However, bio-inspired vehicle colouration was highly intuitive for warning 'non-yielding' Abstract: Various external human-machine interfaces (eHMIs) have been proposed that communicate the intent of automated vehicles (AVs) to vulnerable road users. However, there is no consensus on which eHMI concept is most suitable for intent communication. In nature, animals have evolved the ability to communicate intent via visual signals. Inspired by intent communication in nature, this paper investigated three novel and potentially intuitive eHMI designs that rely on posture, gesture, and colouration, respectively. In an online crowdsourcing study, 1141 participants viewed videos featuring a yielding or non-yielding AV with one of the three bio-inspired eHMIs, as well as a green/red lightbar eHMI, a walk/don't walk text-based eHMI, and a baseline condition (i.e., no eHMI). Participants were asked to press and hold a key when they felt safe to cross and to answer rating questions. Together, these measures were used to determine the intuitiveness of the tested eHMIs. Results showed that the lightbar eHMI and text-based eHMI were more intuitive than the three bio-inspired eHMIs, which, in turn, were more intuitive than the baseline condition. An exception was the bio-inspired colouration eHMI, which produced a performance score that was equivalent to the text-based eHMI when communicating 'non-yielding'. Further research is necessary to examine whether these observations hold in more complex traffic situations. Additionally, we recommend combining features from different eHMIs, such as the full-body communication of the bio-inspired colouration eHMI with the colours of the lightbar eHMI.